Analysis of the Accounting Performance and Cash Generating Power as a Response to Debt Restructuring on the Public Companies in Indonesia - Sutrisno, Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
The objective of this research is to analysis the accounting performance and cash generating power as a response to debt restructuring on the public companies in Indonesia. This research proposed the following hypotheses: 1 ) before conducting the debt restructuring, companies will commit income decreasing earnings management; 2) the companies that conduct debt restructuring, commit the bigger earnings management in the period after debt restructuring than before debt restructuring; 3) the cash generating power in the period after the debt restructuring is higher than that before the debt restructuring; and 4) cash generating power has a better capability than accounting performance in explaining the possibilities for the companies to conduct debt restructuring or not. Logistic regression models are developed to examine the hypotheses capability between accounting performance and cash generating power in explaining the possibilities for the companies to conduct debt restructuring or not. The parameters are estimated by pooled data, which consist of 106 public companies listed in the Jakarta Stock Exchange for the period of 1996 to 2003. The result of the testing shows that empirical evidence supports all the proposed hypotheses, except the hypothesis stating that the cash generating power has a better capability than accounting performance in explaining the possibilities for the companies to conduct debt restructuring or not. Empirical finding of earnings management in the period before and after the companies to conduct debt restructuring will be considered as an input in preparing regulations by regulator. Additional disclosure of the creative accounting practice is expected to increase a transparency of financial statement in order to prevent the emergence of misleading information in earnings management practice by public companies. Key words: accounting performance, cash generating power, debt restructuring, earnings management, and economic crisis.